2015
DOI: 10.1177/0956797614558717
|View full text |Cite
|
Sign up to set email alerts
|

A Second Look at Automatic Theory of Mind

Abstract: In recent work, Kovács, Téglás, and Endress (2010) argued that human adults automatically represented other agents’ beliefs even when those beliefs were completely irrelevant to the task being performed. In a series of 13 experiments, we replicated these previous findings but demonstrated that the effects found arose from artifacts in the experimental paradigm. In particular, the critical findings demonstrating automatic belief computation were driven by inconsistencies in the timing of an attention check, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
73
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 36 publications
3
73
0
Order By: Relevance
“…Ultimately, we intend for these specific discussions to illustrate a broader point: a thorough empirical account of attributions of agency can, and should, play an important role in shaping law and policy about intelligent technologies. potential artifacts in their experimental paradigm (Phillips et al, 2015), there are many similar findings based on different paradigms that also support the idea that children much younger than four years old possess an understanding of false belief (e.g., Onishi & Baillargeon, 2005;Scott, Richman, & Baillargeon, 2015;Yott & Poulin-Dubois, 2012).…”
Section: Introductionmentioning
confidence: 64%
“…Ultimately, we intend for these specific discussions to illustrate a broader point: a thorough empirical account of attributions of agency can, and should, play an important role in shaping law and policy about intelligent technologies. potential artifacts in their experimental paradigm (Phillips et al, 2015), there are many similar findings based on different paradigms that also support the idea that children much younger than four years old possess an understanding of false belief (e.g., Onishi & Baillargeon, 2005;Scott, Richman, & Baillargeon, 2015;Yott & Poulin-Dubois, 2012).…”
Section: Introductionmentioning
confidence: 64%
“…Although many ToM insights are acquired by age 5, mental state understanding continues to grow during middle childhood and adolescence (Hughes, 2016). Furthermore, to be accurate, mental state understanding requires sufficient motivation and engagement of cognitive resources (Phillips et al, 2015), raising an important question about possible factors that affect mentalizing in different social relationships, such as characteristics of the target.…”
mentioning
confidence: 99%
“…This paradigm was successfully adapted to test false belief by Onishi and Baillargeon (2005) who demonstrated that 15-month-old infants looked significantly longer at an incongruent test trial, where an actor's actions were inconsistent with her false belief (searching for an object at the current location), than at a congruent trial (searching at the previous location). These results have been replicated and extended to children as young as 7 months of age using VOE or anticipatory looking procedures (He, Bolz, & Baillargeon, 2011;Kovács, Téglás, & Endress, 2010;Phillips et al, 2015;Scott, Baillargeon, Song, & Leslie, 2010;Senju, Southgate, Snape, Leonard, & Csibra, 2011;Song, Onishi, Baillargeon, & Fisher, 2008;Southgate, Senju, & Csibra, 2007;Surian, Caldi, & Sperber, 2007;Surian & Geraci, 2012;Yott & Poulin-Dubois, 2012). This body of research has provided the foundation for the provocative claim that infants possess an abstract capacity to reason about false beliefs (Baillargeon, Scott, & He, 2010;Scott, 2017;Scott, Richman, & Baillargeon, 2015).…”
Section: Introductionmentioning
confidence: 72%
“…For example, infants might look longer in the incongruent trial of the false belief task because it violates the well-learned rule that people look for objects in the last place they saw them. Others have proposed that infants' looking time patterns in implicit paradigms simply reflect sensitivity to low-level perceptual or attentional factors, and not to an actor's true or false belief about an object's location (Heyes, 2014;Phillips et al, 2015). For example, it has been argued that low-level changes in the properties of the stimuli encoded by the child during the familiarization and belief induction trials (e.g., colors, movements, and shapes) could account for longer looking times during the test trials (Heyes, 2014; but see Scott & Baillargeon, 2014).…”
Section: Introductionmentioning
confidence: 99%